Healthy environments for athleTes (HEAT): environmental conditions along a 90 km ultra-marathon event, South Africa - H. Havenga; D. Gharbi; N. Sewry; B. Language; F. H. Neumann; J. M. Finch; T. Hill; J. Boulter; E. Jordaan; S. J. Piketh; M. Schwellnus; R. P. Burger (International Journal of Biometeorology, 2024)
This paper provides an overview of the HEAT (Healthy Environments for AthleTes) project, which aims to understand the impact of environmental conditions on athlete health and performance during major sporting events such as long-distance running, cycling, and triathlons. In collaboration with the SAFER (Strategies to reduce Adverse medical events For the ExerciseR) initiative, the HEAT project carried out a field campaign at the 2022 Comrades Marathon in the KwaZulu-Natal province of South Africa. The measurement campaign deployed seven weather stations, seven PM 2.5 monitors and one spore trap along the 90 km route to capture spatially representative measurements of complex micro-climates, allergenic aerospora, and particulate matter exposure. The results indicate that runners were exposed to moderate risk heat stress conditions. Novel findings from this initial campaign shows elevated and potentially harmful PM 2.5 levels at spectator areas, possibly coinciding with small fire events around the race day festivities. Our findings show values PM 2.5 levels over the WHO 24-h guidelines at all stations, while 2000 µg/m 3 at two stations. However, the lack of an acute exposure standard means direct health impacts cannot be quantified in the context of a sport event. The HEAT project highlights important aspects of race day monitoring; regional scale climatology has an impact on the race day conditions, the microclimatic conditions (pollution and meteorology) are not necessarily captured by proximity instruments and direct environmental measurements are required to accurately capture conditions along the route.